COMTVal158Met Genotype Affects Complex Emotion Recognition in Healthy Men and Women - Lischke, Alexander; Pahnke, Rike; König, Jörg; Homuth, Georg; Hamm, Alfons O.; Wendt, Julia (Frontiers in Neuroscience, 2019)
The catechol-o-methyltransferase (COMT) gene has repeatedly been shown to change amygdala activity and amygdala-prefrontal connectivity during face processing. Although the COMT gene appears to induce a negativity bias during the neural processing of faces, it is currently unclear whether a similar negativity bias emerges during the behavioral processing of faces. To address this issue, we investigated differences in complex emotion recognition between participants (n = 181) that had been a priori genotyped for functional polymorphisms of the COMT (Val158Met) and serotonin transporter (5-HTTLPR) gene. We were, thus, able to analyze differences in face processing on basis of participants’ COMT genotype while controlling for variations of participants’ 5-HTTLPR genotype. Across a series of well-powered and comparison-corrected analyses, we were able to demonstrate that differences in participants’ COMT but not 5-HTTLPR genotype accounted for differences in participants’ emotion recognition performance. Met/Met carriers and Met/Val carriers were more accurate in the recognition of negative, but not neutral or positive, expressions than Val/Val carriers. We, thus, revealed a similar negativity bias during the behavioral processing of faces that has already been demonstrated during the neural processing of faces, indicating that genotype-dependent changes in catecholamine metabolism crucially affect face processing on the behavioral and neural level.